Comportamiento agronomico del cultivo de remolacha (beta vulgarisL.) con Bio Ezudo,nitropower y produmax - Murillo Sierra, Freddy Eduardo (2012)
This research was to effect in the divine child neighborhood, located in the Canton in San José, Chimbo, Bolívar province. With a length of 129 days in the camp and general objective was to evaluate the agronomic performance of the cultivation of sugar beet (Beta vulgaris) after the implementation of three Biostimulants, organic fertilizers in the production process. The design of blocks at random (D.B.A) with 4 treatments and 6 replicates and a total of 24 plots, 3 meters long and 2 meters wide was used. The results were: the best average length of leaves within 15 days after the first application responds better T3 Nitropower treatment has greater length of leaves with an average of between treatments of 4.77 cm. The length of blade at 60 days, reached the best averages treatment T3 Nitropower with a value of 12. 92 cm, the number of leaves to 15 days after the first application alike on average of 4, so there is no minimal differences and the coefficient of variation is stable, indicating that the biological behavior responds well to all these biostimulants. The number of sheets to 15 days after the second application provides biostimulant Produmax T2 treatment reported a number of 8.42 may indicate the best diameter corresponds to a value of 90.98 treatment T1 Bio Ezkudo mm. In this variable you can specify treatment T1 Bio ezkudo is an average yield between treatments of 3.18 kg, followed by treatment T2 Produmax with 3.83 kg and the T3 Nitropower treatment with 3.14 kg when compared to the witness who reported a value of 3.11 kg.